Cooperation creates selection for tactical deception. - JACKSON, ANDREW (My University, 2013)
Conditional social behaviours such as partner choice and reciprocity are held to be key mechanisms facilitating the evolution of cooperation, particularly in humans. Although how these mechanisms select for cooperation has been explored extensively, their potential to select simultaneously for complex cheating strategies has been largely overlooked. Tactical deception, the mis- representation of the state of the world to another individual, may allow cheaters to exploit conditional cooperation by tactically misrepresenting their past actions and/or current intentions. Here we first use a simple game- theoretic model to show that the evolution of cooperation can create selection pressures favouring the evolution of tactical deception. This effect is driven by deception weakening cheater detection in conditional cooperators, allowing tactical deceivers to elicit cooperation at lower costs, while simple cheats are recognized and discriminated against. We then provide support for our theor- etical predictions using a comparative analysis of deception across primate species. Our results suggest that the evolution of conditional strategies may, in addition to promoting cooperation, select for astute cheating and associated psychological abilities. Ultimately, our ability to convincingly lie to each other may have evolved as a direct result of our cooperative nature.
PUBLISHED
Keywords: reciprocity, Machiavellian intelligence, deceit, comparative analysis, primates; reciprocity, Machiavellian intelligence, deceit, comparative analysis, primates; Neuroscience; Smart & Sustainable Planet